1998
DOI: 10.1159/000069449
|View full text |Cite
|
Sign up to set email alerts
|

CSF-1 (M-CSF) Enhances the Inflammatory Response of Fibronectin-Primed Macrophages: Pathways Involved in Activation of the Cytokine Network

Abstract: We have previously reported that the priming of thioglycollate-elicited peritoneal macrophages (PMφ), as a representative population of mononuclear phagocytes (MNP), by macrophage-colony-stimulating factor (M-CSF or CSF-1) rendered these cells more susceptible to secondary stimulation by extracellular matrix (ECM) proteins, in particular fibronectin (FN), and that at least two β1 integrins, VLA 4 (α4β1 or CD49d) and VLA 5 (α5β1 or CD49e), regulate IL-6 gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…GM-CSF can directly act on PMN by modulating the surface expression of adhesion molecules and increasing neutrophil adherence to the endothelium (Arnaout et al, 1986). It was shown that GM-CSF can induce the expression of IL-6 in monocytes and microglia (Suzumura et al, 1996) and that vice versa IL-6 can inhibit GM-CSF gene expression (Kremlev et al, 1998), presenting a negative feedback system which might explain the fact that the basal GM-CSF mRNA level in uninfected IL-6 ±/± mice was more than twice that in WT controls. Therefore, it was surprising that the increase in GM-CSF mRNA expression was attenuated in infected IL-6 ±/± mice, compared with infected WT mice.…”
Section: Interleukin-6 In Cns In¯ammationmentioning
confidence: 99%
“…GM-CSF can directly act on PMN by modulating the surface expression of adhesion molecules and increasing neutrophil adherence to the endothelium (Arnaout et al, 1986). It was shown that GM-CSF can induce the expression of IL-6 in monocytes and microglia (Suzumura et al, 1996) and that vice versa IL-6 can inhibit GM-CSF gene expression (Kremlev et al, 1998), presenting a negative feedback system which might explain the fact that the basal GM-CSF mRNA level in uninfected IL-6 ±/± mice was more than twice that in WT controls. Therefore, it was surprising that the increase in GM-CSF mRNA expression was attenuated in infected IL-6 ±/± mice, compared with infected WT mice.…”
Section: Interleukin-6 In Cns In¯ammationmentioning
confidence: 99%
“…MCSF expresses high levels and stimulates the expression of other inflammatory molecules during stress or inflammation. 68 Angiogenesis is essential for blood circulation and communication between tissues and cells. Exotoxin is a hematopoietic stem cell-derived proangiogenic factor necessary for neovascularization and reduces the inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings also show that autocrine activation of CSF1R promotes lymphoma growth in the absence of exogenous CSF1. CSF1 is posttranslationally modified and often retained within the extracellular matrix, and may be difficult to detect in plasma (66,67), and could explain why CSF1 was rarely detected in plasma from TCL patients (data not shown). Future studies will be needed in a larger cohort of patients to examine the extent to which CSF1R expression is associated with disease natural history or response to therapy.…”
Section: Discussionmentioning
confidence: 99%